KAJIAN KUALITAS AIR SUNGAI BENING SEBAGAI SUMBER AIR IRIGASI PERSAWAHAN DI DESA MOPUYA SELATAN II KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Hendra Yusuf; Sofia Wantasen; Adeleyda M. W. Lumingkewas (COCOS, 2018)
ABSTRACT  The purpose of this study was to determine the water quality of Bening River in Subdistrict Dumoga Utara District Bolaang Mongondow which would be used as rice field irrigation water in the South Mopuya II Village, Subdistrict Dumoga Utara District Bolaang Mongondow. The study was conducted for three months (3 months), namely April to June, the location of water sampling is the Bening River in South Mopuya II Village, then analyzed in the Water Quality Laboratory. The results of the analysis show that the Bening River Sodium Adsorption Ratio (SAR) concentration in the Upper Area (0.61), in theBening River Lower Area (0.59), is in good quality.  DHL (Electrical Conductivity) concentrations in the Bening River in the Upper Area (2.39.10-5dS/m), in the Bening River Lower Area (2.59.10-5dS/m), are in good quality.  TDS (Total Dissolved Solid) concentration in the Bening River in the Upper Area (167 mg/l), in the Bening River Lower Area (181 mg/l), in good quality. Chloride (Cl) Concentration on Bening River in the Upper Area (0.031 me/l), in the Bening River Lower Area (0.051 me/l), in good quality. Boron (B) Concentration on Bening River in the Upper Area (0.005 mg/l), in the Bening River Lower Area (0.005 mg/l), in good quality.  Nitrate (NO3) concentrations in the Bening River in the Upper Area (0.147 me/l), in the Bening River Lower Area (0.179 mg/l), in the good category.  pH concentration in the Bening River in the Upper Area (8.19), in the Bening River Lower Area (7.55), in good quality.  The results of the analysis of Bening River water quality are still in good category or meet the requirements in accordance with the value of Irrigation Water Quality Standards Ayers and Wetscot, 1985.  Keywords:, Water Quality, Sungai Bening, Irigation Water.